The Possibilities of Forensic Financial and Credit Еxamination in Banking Fraud Investigations - M. G. Nersesyan (Теория и практика судебной экспертизы, 2017)
One type of forensic examination most commonly requested in the investigation of banking fraud is forensic accounting analysis, which includes forensic financing audit. The paper examines special considerations in requesting and conducting this type of forensic analysis, as well as its objectives. Selected case studies illustrate the possibilities of forensic financing audit of official and unofficial (off-the-books) financial records of a criminal association, as well as the scope of a forensic accountant's competence in determining the revenue or size of the premium received for conducting illegal banking transactions.